Strategi Manajemen Krisis Public Relations Badan Amil Zakat Nasional Republik Indonesia: Studi Kasus Fenomenologi Penerimaan Donasi McDonald’s Indonesia untuk Palestina - Astrid Marliana Raida; Nani Nurani Muksin (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
This research is motivated by the crisis of public trust experienced by the National Zakat Agency of the Republic of Indonesia (BAZNAS RI) following the receipt of a donation of Rp1.5 billion from McDonald's Indonesia, which is considered to be affiliated with the Israeli McDonald's chain. This crisis has led to public rejection and questions about BAZNAS RI's credibility as a national zakat management institution. This research aims to: (1) analyze the crisis management strategies implemented by the Public Relations division of BAZNAS RI, and (2) examine the forms of crisis response strategies used in handling the issue. The theory used is Situational Crisis Communication Theory (SCCT), with a qualitative approach and phenomenological method. Data collection techniques were carried out through interviews and observations. The results of the study indicate that BAZNAS RI Public Relations implemented three stages of crisis management strategies, namely pre-crisis, during crisis, and post-crisis. In the pre-crisis stage, media monitoring, internal meetings, and the formation of a crisis communication team were conducted. In the crisis stage, strategic steps were taken through coordination with partners, issuing official statements, terminating cooperation with McDonald's Indonesia, and publishing positive content. Support from public figures was also leveraged to restore the organization's image. In the post-crisis phase, issue monitoring and evaluation of collaboration partners were conducted. The response strategy focused on a rebuilding and bolstering approach through apologies, strengthening a positive image, and affirming humanitarian values. These findings underscore the importance of empathetic, transparent, and value-oriented communication in addressing the crisis of trust in philanthropic institutions.